Implementation of Demonstration Method to Improve Student Learning Outcomes in Fiqh Subject at MI Miftahun Najah Banyuputih Situbondo - Nailatul Jazilah (Journal of Action Research in Islamic Education, 2025)
The main problem of this research is the low learning outcomes of students in grade III of MI Miftahun Najah Banyuputih in the Fiqh subject, the topic of tarawih and witir prayers. A Classroom Action Research (CAR) has been conducted which aims to improve students' learning outcomes in the Fiqh subject, the topic of tarawih and witir prayers through the application of the demonstration method in grade III of MI Miftahun Najah Banyuputih. This research was carried out in two cycles, each cycle consisting of four stages, namely: planning, implementation of actions, observation and reflection, with a total of 21 students consisting of 15 boys and 6 girls. From the results of the final evaluation of cycle I, the classical learning completeness was obtained by 48% with an average value of 65.7. The results of the final evaluation of cycle II obtained classical learning completeness of 76%, with an average value of 77.3. It can be concluded that the application of the demonstration method can improve students' learning outcomes in the Fiqh subject, the topic of tarawih and witir prayers in grade III of MI Miftahun Najah Banyuputih.